2017
DOI: 10.17811/rifie.46.2.2017.73-82
|View full text |Cite
|
Sign up to set email alerts
|

La educación emocional en la infancia: una estrategia inclusiva

Abstract: IntroducciónLa UNESCO define la inclusión educativa como "un proceso de abordaje y respuesta a la diversidad de las necesidades de todos los alumnos a través de la creciente participación en el aprendizaje, las culturas y las comunidades, y de la reducción de la exclusión dentro y desde la educación" (2005, p. 13). Como responsabilidad del sistema educativo, implica la introducción de cambios en los enfoques y en las estructuras, a fin de garantizar la educación y la efectiva participación de la totalidad del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
1
Order By: Relevance
“…Garberoglio, Gobble, and Cawthon [49] (p. 378) reported that teacher training and school settings might prioritize "instructional strategies and classroom management over student engagement." However, scholars argue that the most important learning (i.e., most likely to convey flexible understanding) occurs when learners engage in solving tasks that pose challenges [2][3][4][5][6][7][8]50]. Furthermore, significant learning also occurs when students with hearing loss listen to the ideas of their peers as a way of improving their own thinking about a task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garberoglio, Gobble, and Cawthon [49] (p. 378) reported that teacher training and school settings might prioritize "instructional strategies and classroom management over student engagement." However, scholars argue that the most important learning (i.e., most likely to convey flexible understanding) occurs when learners engage in solving tasks that pose challenges [2][3][4][5][6][7][8]50]. Furthermore, significant learning also occurs when students with hearing loss listen to the ideas of their peers as a way of improving their own thinking about a task.…”
Section: Discussionmentioning
confidence: 99%
“…Schools that support IE for children who use hearing assistive devices presumably offer an appropriate curriculum for their respective age groups, with curricular adaptations to improve the academic performance [7]. The school curriculum uses a philosophy based on essential IE concepts for giving extra support for children with hearing loss (e.g., collaboration with all human beings, the development of students' self-concept, or the cognitive and emotional competencies of students) [8]. This set of logical reasoning involved identifying core interdisciplinary concepts that facilitated the inclusion of all the students of 3rd Compulsory Secondary Education [9].…”
Section: Collaborative Teamwork In a School Centrementioning
confidence: 99%
“…Junto a lo expuesto, se pone de manifiesto la inclusión de competencias que aludan a la capacidad docente para crear un entorno socioemocional adecuado. El profesorado excelente se caracteriza por establecer un ambiente de afecto, seguridad, confianza y participación que contribuye al aprendizaje y desarrollo de la infancia (Cepa-Serrano et al, 2017). De este modo, se fomenta en la infancia su autonomía respecto a la toma de decisiones y la asunción de responsabilidades (González-Alfaya et al, 2021).…”
Section: Discusión Y Conclusionesunclassified
“…La inteligencia emocional está presente, al gestionar las habilidades interpersonales en la interacción social (Bisquerra et al, 2015). Habilidades expuestas también en el currículo como competencia emocional (Cepeda et al, 2017).…”
Section: Habilidades Sociales Aprendizaje Cooperativo Y Necesidades Educativas Específicasunclassified